Probiotic Gummies for Improving Gut Microbiota and Nutritional Status in Stunted Children: A Narrative Review - Rusmayanti, Agustina; Kasasiah, Ahsanal; Irgi, Khaeru (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Stunting remains a major nutritional problem in Indonesia and is often linked to gut microbiota imbalance that can limit nutrient absorption and weaken intestinal function. This article reviews evidence on how probiotics can support gut health and examines the potential of gummy formulations that children can consume easily. The review process used Publish or Perish to search scientific articles from 2016 to 2025 in Google Scholar, PubMed and Scopus. Titles, abstracts and full texts were screened to ensure relevance. A total of 17 studies were included in the analysis. The findings show that probiotics can increase SCFA-producing bacteria, improve the gut mucosal barrier and support the absorption of minerals such as calcium and iron. Several studies also report better digestive comfort and improved microbiota diversity after probiotic intake. Probiotic gummies show good stability, maintain viable cells and are well accepted by children, which makes them a practical delivery system. The evidence from these 17 studies suggests that probiotic gummies have potential to support gut health and contribute to stunting prevention. Longer studies are still needed to measure their direct impact on child growth and guide future nutritional interventions.